Z dependence of atomic-field bremsstrahlung - Semaan, Mars (1982)
New results for the atomic-field bremsstrahlung for Z=80 are presented which, along with an extension of previous results for Z=10 to 54 to lower radiated-photon energies, can be compared with theory. The results are in very good agreement with theory and suggest that there is no evidence for the onset of two-photon processes for Z=80.